Pengaruh Variabel Pemoderasian Dalam Hubungan Financial Leverage Terhadap Dividend Payout - Nicholas Chandra, Elsa Imelda (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The objective of this research is to obtain empirical evidence about the effect of financial leverage toward dividend payout moderated by business risk, firm size, growth opportunity, liquidity, profitability, tangibility, and non-debt tax shield. This research uses secondary data. The object of this research is property and real estate companies listed in the Indonesian Stock Exchange (IDX) during the year 2016-2018. This research is conducted with 39 property and real estate companies as the sample. Furthermore, the data collection technique that is used in this research is purposive sampling in which data is processed using EVIEWS 10 program. The results of this research show that financial leverage has a significant effect toward dividend payout, firm size and profitability can moderate the positive effect of financial leverage toward dividend payout, while business risk, growth opportunity, liquidity, tangibility, and non-debt tax shield do not have significant effect toward dividend payout.